Analisis Saluran Pemasaran Kelapa Di Desa Pinilih Kecamatan Dimembe Kabupaten Minahasa Utara - Vega C. Sengkey; Tinneke M. Tumbel; Lucky F. Tamengkel (Universitas Sam Ratulangi, 2018)
This study aims to determine and analyze how the marketing channels of copra agricultural products from producers to consumers as a reference for determining the amount of marketing margin for each copra marketing agency from producer to consumer, and the percentage of prices received by farmers (Farmer's Share) in Pinilih Village Dimembe District, North Minahasa Regency. The research method used in this research is descriptive quantitative research method or survey method, which is focused on the real and actual picture of a problem then collected, compiled and analyzed. Samples taken as respondents were 79 craftsmen, while the number of collectors was 4 people. The results of the analysis show that: There are two copra marketing channels from Pinilih Village, Dimembe District, North Minahasa Regency to the final consumer (oil factory) Marketing channel I: Farmers, Consumers. Marketing channel II: Farmers, Collectors, Consumers. And the most widely used by copra farmers in Pinilih Village, Dimembe Subdistrict, North Minahasa Regency, namely marketing channel II, in this marketing channel, there is an intermediary trader, namely collecting traders, by means of collecting traders directly to the farmer's house and then selling it to the final consumer (oil mill). The marketing margin can be known in the marketing channel I have a marketing margin of Rp. 3,000 per kg which is higher than the second channel of Rp. 2,500 per kg. From the calculation results obtained by the value of Farmer's second share of the marketing channel, namely marketing channel I by 100 percent, meaning that the price received by farmers in marketing channel I is 100 percent of the price paid by the consumer, and for marketing channel II is 66.67 percent, meaning that the price received by farmers is 66.67 percent of the price paid by consumers. According to the author's observation, it can be suggested to copra farmers in Pinilih Village, Dimembe Subdistrict, North Minahasa Regency to be able to sell their copra directly to the end consumer (industry).Keywords: Marketing Channels